2020
DOI: 10.1111/jfpp.14841
|View full text |Cite
|
Sign up to set email alerts
|

Determination of antioxidant and antimicrobial activity of Herby cheese

Abstract: Herby cheese is a kind of traditional Turkish cheese, produced in Van, Bitlis, Siirt, Batman, Ağrı, and Diyarbakır province and is semihard, salty, and containing endemic herbs belong to the region (Ocak & Kose, 2015). In Herby cheese production, the raw milk of sheep and mixture of cow and goat milk are used along with the addition of herbs (Alemdar & Agaoglu, 2010) such as sirmo (Allium vineale L.), mendi (Chaerophyllum macropodum Boiss.), and siyabo (Ferula rigidula DC.) (Kose, 2015). The herbs give the che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 36 publications
2
6
0
2
Order By: Relevance
“…In the CUPRAC method, antioxidant activity of black cumin-rosemary-containing samples (2 and 5) had increased during the storage period. Similar to this, Gupta et al (2009), Kose and Ocak (2020) and Huma et al (2018) reported that TEAC values of cheeses were increased during maturation.…”
Section: Antioxidant Activitysupporting
confidence: 83%
See 4 more Smart Citations
“…In the CUPRAC method, antioxidant activity of black cumin-rosemary-containing samples (2 and 5) had increased during the storage period. Similar to this, Gupta et al (2009), Kose and Ocak (2020) and Huma et al (2018) reported that TEAC values of cheeses were increased during maturation.…”
Section: Antioxidant Activitysupporting
confidence: 83%
“…Similar to this, Gupta et al . (2009), Kose and Ocak (2020) and Huma et al . (2018) reported that TEAC values of cheeses were increased during maturation.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations